The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2527/tas2017.0074
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among early postmortem loin quality and aged loin and pork chop quality characteristics between barrows and gilts

Abstract: Rapid assessment of pork quality by packers necessitates using early postmortem (∼1 d) traits as an indication of aged pork quality (∼14 d). Efforts have been made to develop a grading system based on color and marbling of the ventral side of boneless loins. In order for this system to be successful, there must be a correlation between early postmortem quality traits observed by packers and the same traits observed by consumers after aging. However, the strength and direction of those correlations are unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Lowell et al (2017) reported that early postmortem (1 d) loin pH was strongly correlated with aged pH (r = 0.80 barrows; 0.75 gilts). Early pH was moderately correlated with aged ventral L* (r = −0.57 barrows; −0.54 gilts), aged subjective ventral color (r = 0.55 barrows; 0.41 gilts), and aged subjective chop color (r = 0.42 barrows; 0.44 gilts) (Lowell et al, 2017). Early ventral L* was moderately correlated with aged ventral L* (r = 0.60 barrows; 0.51 gilts) (Lowell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lowell et al (2017) reported that early postmortem (1 d) loin pH was strongly correlated with aged pH (r = 0.80 barrows; 0.75 gilts). Early pH was moderately correlated with aged ventral L* (r = −0.57 barrows; −0.54 gilts), aged subjective ventral color (r = 0.55 barrows; 0.41 gilts), and aged subjective chop color (r = 0.42 barrows; 0.44 gilts) (Lowell et al, 2017). Early ventral L* was moderately correlated with aged ventral L* (r = 0.60 barrows; 0.51 gilts) (Lowell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of independent correlation coefficients between Pietrain-sired pigs and Duroc-sired pigs were achieved following the example of Kenny (1987) and Lowell et al (2017) using a z-test for comparing 2 independent correlations. First, data were grouped into 2 individual data sets by sire line (Pietrain-sired pigs and Duroc-sired pigs).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations